Tissue culture technician and in vitro screening of rice (Oryza sativa L) callus for salt tolerance - Arshad Alhasnawi (Journal of Global Pharma Technology, 2018)
World wide, the most important cereal crop is rice (Oryza sativa L.) However, its production goes through from salty environments in several areas since it is one of the salt perceptive crops. NaCl mainly contributes salinity that is one of the significant abiotic stress aspects and, the leading cause of crop failure in the world. Tissue and cell culture methods have been applied to gain salt tolerant plants through using in vitro culture methods. In the present paper, the vitro screening of plant germplasm for salt tolerance, as a successful employment of this technique in rice is raised. The current review, focus on plant tissue culture as a method applied for in vitro to protocol for callus induction and screening of salt tolerance and revival of rice in the laboratory.